Sensory profiles and immune-related expression patterns of patients with and without neuropathic pain after peripheral nerve lesion - Held, Melissa; Karl, Franziska; Vlckova, Eva; Rajdova, Aneta; Escolano-Lozano, Fabiola; Stetter, Christian; Bharti, Richa; Förstner, Konrad U; Leinders, Mathias; Dušek, Ladislav; Birklein, Frank; Bednarik, Josef; et al. (Pain, 2019)
In this multicenter cross-sectional study, we determined sensory profiles of patients with (NL-1) and without neuropathic pain (NL-0) after nerve lesion and assessed immune-related systemic gene expression. Patients and matched healthy controls filled in questionnaires and underwent neurological examination, neurophysiological studies, quantitative sensory testing, and blood withdrawal. Neuropathic pain was present in 67/95 (71%) patients (NL-1). Tactile hyperalgesia was the most prominent clinical sign in NL-1 patients (P < 0.05). Questionnaires showed an association between neuropathic pain and the presence of depression, anxiety, and catastrophizing (P < 0.05 to P < 0.01). Neuropathic pain was frequently accompanied by other chronic pain (P < 0.05). Quantitative sensory testing showed ipsilateral signs of small and large fiber impairment compared to the respective contralateral side, with elevated thermal and mechanical detection thresholds (P < 0.001 to P < 0.05) and lowered pressure pain threshold (P < 0.05). Also, more loss of function was found in patients with NL-1 compared to NL-0. Pain intensity was associated with mechanical hyperalgesia (P < 0.05 to P < 0.01). However, quantitative sensory testing did not detect or predict neuropathic pain. Gene expression of peptidylglycine α-amidating monooxygenase was higher in NL patients compared with healthy controls (NL-1, P < 0.01; NL-0, P < 0.001). Also, gene expression of tumor necrosis factor-α was higher in NL-1 patients compared with NL-0 (P < 0.05), and interleukin-1ß was higher, but IL-10 was lower in NL-1 patients compared with healthy controls (P < 0.05 each). Our study reveals that nerve lesion presents with small and large nerve fiber dysfunction, which may contribute to the presence and intensity of neuropathic pain and which is associated with a systemic proinflammatory pattern.
Keywords: Young Adult; exprese genu; Cross-Sectional Studies; Gene Expression; Male; kohortové studie; mladý dospělý; Cohort Studies; Adolescent; katastrofizace; mediátory zánětu; Neuralgia; Catastrophization; měření bolesti; Adult; Aged; dospělí; mužské pohlaví; senioři; nervová vlákna; Nerve Fibers; mladiství; senioři nad 80 let; lidé; ženské pohlaví; Humans; průřezové studie; Aged, 80 and over; Inflammation Mediators; Female; Pain Measurement; lidé středního věku; neuralgie; Middle Aged